Dynamic crushing and energy absorption of regular, irregular and functionally graded cellular structures - Ajdari, Amin; Nayeb-Hashemi, Hamid; Vaziri, Ashkan (International journal of solids and structures, 2011)
The in-plane dynamic crushing of two dimensional honeycombs with both regular hexagonal and irregular arrangements was investigated using detailed finite element models. The energy absorption of honeycombs made of a linear elastic-perfectly plastic material with constant and functionally graded density were estimated up to large crushing strains. Our numerical simulations showed three distinct crushing modes for honeycombs with a constant relative density: quasi-static, transition and dynamic. Moreover, irregular cellular structures showed to have energy absorption similar to their counterpart regular honeycombs of same relative density and mass. To study the dynamic crushing of functionally graded cellular structures, a density gradient in the direction of crushing was introduced in the computational models by a gradual change of the cell wall thickness. Decreasing the relative density in the direction of crushing was shown to enhance the energy absorption of honeycombs at early stages of crushing. The study provides new insight into the behavior of engineered and biological cellular materials, and could be used to develop novel energy absorbent structures.